Perception of paintball players towards leadership characteristics - Jaafar, Iqwan Alif (2019)
The purpose of this research is to study the perceptions of paintball players towards leadership characteristics. The instrument used in the study was a structured questionnaire. The questionnaire consists three sections; (i) demographic profiles, (ii) the involvement in paintball activity and (iii) the leadership in paintball activity. This study was considered on several impacts on the leadership characteristics by the doing paintball activity. From the findings, the percentage of positive impacts of paintball activity towards leadership characteristics is higher than negative. In addition, the results of this study may be used by the government, authorities, paintball communities and paintball parks to develop more paintball activities and parks to develop leadership characteristics.